Evaluation of Rabbit Skin Gelatin and Preparation of Yogurt using Rabbit Skin Gelatin: Rabbit Skin Gelatin and its Aplication in Yogurt - Pancapalaga, Wehandaka; Khotimah, Khusnul; Hartati, Endang Sri (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
TThe purpose of this research is to know the quality of rabbit skin gelatin soaked in the concentration of different acetic acid as well as its application in yogurt making. Compared to the use of the Arab Gum and CMC (Carboxymethyl Cellulose) The material used in this study was the rabbit skin type Rex male. The treatment of this research is the immersion of acetic acid with 2 %; 3 %; 4 %; 5 % concentration. The results showed that concentrations of acetic acid solution in the process of soaking of acid extract gave a very significant effect (p < 0.01) toward yield, pH, protein, fat, viscosity, gel strength, the melting point of rabbit skin gelatin. Application of rabbit skin gelatin on yogurt making gives better yogurt quality compared with the addition of Arabic Gum or CMC. The results showed that the various stabilizers in the yogurt-making process give significant effect (p < 0.01) to the resulting pH, The power of the water belt, Synergized, Viscosities of yogurt. However, the various stabilizers in the yogurt-making process give a non-significant effect (p > 0.05) to the resulting acidity of yogurt. The conclusion to immersion acetic acid with a concentration of up to 5% will improve the quality of the rabbit skin gelatin and the use of rabbit skin gelatin by 0.8 % as a stabilizer in the manufacture of yogurt produces a better-quality yogurt compared to the Arabic Gum and CMC (Carboxymethyl Cellulose).